Countercyclical versus Procyclical Taylor Principles - Jean-Bernard Chatelain; Ralf Kirsten (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Assuming inflation is a forward variable in Taylor (1999) model, this paper finds opposite policy rule recommandations with counter-cyclical policy rule parameters (Taylor principle: inflation rule larger than one and bounded upwards) in the case of optimal policy under commitment versus pro-cyclical policy rule parameters (inflation rule parameter below zero) in the case of discretionary policy. For the observed high inertia of the Fed with variations of the nominal policy rate within the range [0%,4%] during the great moderation, the cost of time-inconsistency is negligible for optimal policy. Time-inconsistency cannot be the ultimate argument to reject counter-cyclical Taylor principle.
Keywords: C6; E4; E5; 330; Monetary policy; Optimal policy under commitment; Time consistent discretionary policy; Taylor rule; Monetary policy; Stabilization policy